A rapid mixed-methods assessment of Libya’s primary care system - Allen, LN; Hatefi, A; Kak, M; Herbst, CH; Mallender, J; Karem, G (BioMed Central, 2024)
Background: Libya has experienced decades of violent conflict that have severely disrupted health service delivery. The Government of National Unity is committed to rebuilding a resilient health system built on a platform of strong primary care. Aim: Commissioned by the government, we set out to perform a rapid assessment of the system as it stands and identify areas for improvement. Design and setting: We used a rapid applied policy explanatory-sequential mixed-methods design, working with Libyan data and Libyan policymakers, with supporting interview data from other primary care policymakers working across the Middle East and North Africa region. Method: We used the Primary Health Care Performance Initiative framework to structure our assessment. Review of policy documents and secondary analysis of WHO and World Bank survey data informed a series of targeted policymaker interviews. We used deductive framework analysis to synthesise our findings. Results: We identified 11 key documents and six key policymakers to interview. Libya has strong policy commitments to providing good quality primary care, and a high number of health staff and facilities. Access to services and trust in providers is high. However, a third of facilities are non-operational; there is a marked skew towards axillary and administrative staff; and structural challenges with financing, logistics, and standards has led to highly variable provision of care. Conclusion: In reforming the primary care system, the government should consolidate leadership, clarify governance structures and systems, and focus on setting national standards for human resources for health, facilities, stocks, and clinical care.